Transformation of Collaborative Project-Based Learning to Improve 21st Century Learning Outcomes in the Society 5.0 Era - Diqi Arian; Paus Iskarni; Dedi Hermon (Jurnal Penelitian Pendidikan IPA, 2025)
The Society 5.0 era demands educational innovation that integrates technology, collaboration, and complex problem solving into the learning process. This study aims to analyze the effectiveness of implementing a project-based collaborative learning model on improving student learning outcomes and 21st-century skills in geography. The research used a Classroom Action Research (CAR) approach in two cycles, which included planning, action, observation, and reflection. The research subjects consisted of 67 grade XI phase F students at SMAN 1 Siak, Siak Regency, Riau Province, in the 2023–2024 academic year, who were randomly divided into experimental and control groups. The results showed that the experimental group experienced a significant increase in their understanding of geography concepts with an increase of 41.74%, p < 0.05, while the control group only increased by 4.49%, p > 0.05. In addition, 88.6% of students in the experimental group achieved the “very good” category in 21st-century skills, particularly in collaboration, critical thinking, communication, and creativity. Thus, the project-based collaborative learning model has been proven effective in transforming geography learning and is recommended as an innovative strategy to address educational challenges in the Society 5.0 era